2019
DOI: 10.3233/jifs-179087
|View full text |Cite
|
Sign up to set email alerts
|

Economic benefit analysis of green building based on fuzzy logic and bilateral game model

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…In order to validate the stability of the evolution of green housing market subject behavior, the replicator dynamical system was assigned with numerical values for numerical simulation analysis. The determination method of numerical value is similar to the method of numerical selection in references [ 20 22 ], which is to obtain first-hand data by investigating consumers, developers, and leaders of government departments, and comparing the dimensions of the data to obtain the relative value [ 26 ]. Due to the limited length, this study selected numerical values, where A P = 50, A Z = 40, θ = 0.5, D 2 = 40, A Q = 30, C Z = 50, φ = 0.5, S Z 1 = 30, η = 0.5, S Z 2 = 30, G 1 = 160, and D 1 = 90.…”
Section: Numerical Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to validate the stability of the evolution of green housing market subject behavior, the replicator dynamical system was assigned with numerical values for numerical simulation analysis. The determination method of numerical value is similar to the method of numerical selection in references [ 20 22 ], which is to obtain first-hand data by investigating consumers, developers, and leaders of government departments, and comparing the dimensions of the data to obtain the relative value [ 26 ]. Due to the limited length, this study selected numerical values, where A P = 50, A Z = 40, θ = 0.5, D 2 = 40, A Q = 30, C Z = 50, φ = 0.5, S Z 1 = 30, η = 0.5, S Z 2 = 30, G 1 = 160, and D 1 = 90.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…Feng et al [ 21 ] found the interest equilibrium point among green building stakeholders (government, construction units and consumers) by building a game model, so as to provide reference for the development of green building led by the government. Chen [ 22 ] analyzed the economic benefits of green building by building a bilateral game model between green building developers, consumers, and the government. The research found that the incremental profit of developers is the primary factor affecting enterprise decision-making, followed by the government's incentive policy, and the final strategic choice will be stabilized to higher economic benefits.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there may be value investors based on the value of the company in the market, technical investors based on price movements, and new investors who make transactions based on news. Similarly, the diversity of the exchange comes from the diversity of the way it generates orders: the diversity of the subject matter of the exchange and the diversity of the subject matter processing methods [22]. However, from a macroperspective, various investor entities and various exchange entities have a commonality in processing news and then acting on assets based on the news.…”
Section: Market Participation Eme Model Constructionmentioning
confidence: 99%
“…For a long time, electricity has been regarded as an important basic industry related to the national economy and people's livelihood, and it is an indispensable basic element for people's production and life to proceed in an orderly manner [1][2][3]. e deepening of industrialization and urbanization has led to a rapid increase in the demand for electricity, and the proportion of electricity in the consumption of terminal energy (that is, the energy that users can directly use without any treatment) is increasing [4]. e distribution network is an important part of the national power grid, and the direct service targets are users.…”
Section: Introductionmentioning
confidence: 99%